Perizinan Tambang Terbuka di Kawasan Taman Wisata Alam Seblat : Apakah Sudah Tepat? - Saputra, Dendi; Salsabilla Putri, Indah; Ajian Putra, Deyan; Iskandar; Elca Putera, Arie (Veteran Law Review, 2025)
There are often conflicts between economic and conservation interest such as the establishment of mining licenses in conservation area. This qualitative study aims to analyze the validity of open pit mining permit number I.315.DESDM in the conservation area of Seblat Nature Tourism Park, North Bengkulu. This study is a normative legal research that uses literature study as a data collection method. The data obtained is analyzed, systematized with deducative thinking method. The results of this study found that mining business license number I.315.DESDM is not accordance with the function of conservation areas because it contradicts Law No. 5 of 1990 and Government Regulation No. 7 of 1999 and contains juridical defects both in terms of authority and procedure. Following up on these findings, BKSDA through the Ministry of Environment and Forestry can submit a recommendation to review the mining business license (IUP) number I.315.DESDM to the Ministry of Energy and Mineral Resourses (ESDM).